'Resistance was futile!' Cycling's discourses of resistance to UK automobile modernism 1950–1970. (3rd April 2018) - Parsons, Rorie; Vigar, Geoff
ABSTRACT: This paper investigates the place of utility cycling (cycling as a means of transport rather than as a sport or leisure activity) under urban modernism in the UK. In many western contexts the dominant feature of urban modernism was its emphasis on accommodating private vehicles to the neglect of other forms of mobility. The result was the production of a 'car-system' with significant change to urban and rural environments. This paper assesses resistance to what we term 'automobile modernism' during the high watermark of its planning and implementation (1950–1970), using the UK Cyclists' Touring Club (now known as Cycling UK) archive. We make three contributions. First, and primarily, we highlight how cycling advocacy contested automobile modernism's claim that cycling was 'outmoded'. In so doing we note significant continuity in policy debates and political advocacy regarding cycling's place in the road environment around issues such as segregation from motor vehicles. Contemporary attempts to promote cycling, as well as a wider urban sustainability agenda, are heavily influenced by this history. Second, we highlight a commonality between cycling and other resistance to automobile modernism in terms of rural and urban landscape impacts. Third, we highlight how the CTC 'professionalized' its advocacy to resist automobile modernism.